The Interventional Capacity of Community Health Volunteers for Screening and Linkages of Non-Communicable Diseases in Nyeri County, Kenya - Langakuo, Kenneth; Nyaberi, Jackline; Echoka, Elizabeth (Global Journal of Health Sciences, 2024)
Purpose: Non-communicable diseases (NCDs) are a significant global health challenge, contributing to 50% of worldwide morbidity and 63% of mortality. The burden is particularly substantial in low"”and middle-income countries (LMICs), where 80% of NCD-related deaths occur. This study evaluated barriers and challenges to effective screening and linkages of NCDs in Nyeri County. Methodology: A quasi-experimental non-equivalent pre-and post-test design was conducted from May 2022 to March 2023. The study employed multistage cluster and random sampling to select ten community units, resulting in 150 community health volunteers (CHVs) in the control unit and 150 in the intervention group. Data collection was facilitated through the KOBO app. Quantitative data was analyzed using SPSS version 28.0, and qualitative data was audio-recorded, transcribed, and analyzed via N-Vivo 12 and findings were presented in textual descriptions and thematic analysis that included direct quotes from participants, descriptions of observed behaviors, and interpretations of patterns and themes. Findings: The study shows that 59.3% of respondents have minimal information, and 92.7 % (n =139) have no clear understanding of NCDs, with a pre-intervention capacity of 48.8%. Independent sample t-test showed a significant difference in capacity from a pre-intervention average of 48.75 (SD±5.7) %, which increased to 68.28 (SD±7.6) %, p<0.001. Unique Contribution to Theory, Practice and Policy: There is a need for a comprehensive, and culturally sensitive training for that will focus on modern healthcare practices, implementing more structured, community-centric approaches involving effective communication, mobilization, and sensitization will enhance the capacity and acceptance of CHVs' roles in combating NCDs. Continuous research and evaluation should ensure practical changes including innovations and use of mobile apps like NCDs app and wheel. An easy-to-use CHV mobile app, continuous capacity building and increased awareness and training will greatly improve on CHVs screening and linkages. Therefore, in this era of technology and use of mobile phones, there is need to develop an app that can be integrated with CHVs mobile phones, Healthcare facility and clients for close NCD monitoring and referral.